(untitled) (Research, Society and Development, 2022)
Peppermint (Mentha piperita) is one of the most popular and used plant species in the world in its various commercially available forms, such as tea leaves, essential oils and extracts. It has a range of actions in the body, and can be used to treat headaches, gastrointestinal disorders and respiratory deficiencies, in addition to helping with biliary disorders, dyspepsia and enteritis. The aim of this study was to evaluate the quality of peppermint samples sold in different herbalists located in Feira de Santana, Bahia. Four samples were analyzed (in bulk and in sachets), using tests of organoleptic characteristics, moisture content, total ash and presence of foreign materials. Most of the samples do not present satisfactory results, deviating from the standards established in the literature. Samples A and B (bulk) failed in the foreign material, total ash and moisture content tests, while C (sachet) failed in ash content and D (sachet) in foreign matter and total ash. Samples that suffer quality deviation are subject to loss of effectiveness and potential induction of poisoning.